Episodic Meso-Cenozoic denudation of Chinese Tianshan: evidence from detrital apatite fission track and zircon U–Pb data, southern Junggar Basin margin, NW China. (15th May 2019) - Xiang, Dunfeng; Zhang, Zhiyong; Xiao, Wenjiao; Zhu, Wenbin; Zheng, Dewen; Li, Guangwei; Zheng, Bihai; Song, Dongfang; Han, Chunming; Pang, Jianzhang
Graphical abstract: Highlights: Oligocene-Pliocene sediments in north Junggar mainly sourced from North Tianshan. Accretion of Cimmerian blocks triggered two episodes of Mesozoic cooling in Tianshan. Onset of the modern Tianshan orogeny commenced in Late Oligocene-Early Miocene time. Ongoing India indentation caused rapid cooling between 11–3 Ma by stress propagation. Abstract: It is generally accepted that the Tianshan was reactivated repeatedly throughout Meso-Cenozoic time. However, the extent of these episodes has not been fully understood. Using a previous magnetostratigraphic baseline, this study reports a detrital zircon U–Pb and apatite fission track dating study along the 4 km thick Cenozoic Jingou River section at the southern margin of the Junggar Basin. Our results provide direct insight into the denudation history of the bordering Tianshan Mountains and suggest that they experienced two phases of rapid cooling in the Jurassic and Cretaceous. These cooling phases are attributed to tectonic events at distant plate margins such as the Late Triassic-Cretaceous accretion of peri-Gondwanan blocks (e.g. Qiangtang and Lhasa). The detrital zircon U–Pb ages range widely from ∼58 to 3055 Ma with a majority falling between ∼58 and 600 Ma. They can be statistically separated into two primary age peaks at 300–290 Ma and 450–410 Ma, as well as two secondary peaks at 170 Ma and 850 Ma. Detrital zircon U–Pb dating results suggest that the Central Tianshan may have still shed detritus into the Junggar Basin during the Early Palaeogene. In the Late Oligocene-Early Miocene, the modern North Tianshan started to form a topographic barrier that blocked all northward rivers flowing from the Central Tianshan to the Junggar Basin. Progressive northward indentation of India into Eurasia, caused a final intense phase of cooling and denudation of the Tianshan between ∼11 and 3 Ma, leading to deposition of the Xiyu Formation, a widely distributed thick conglomerate.